Minutes of 22nd technical and progress monitoring (TPM) meeting of BRACU new campus (session I) - Brac University (Brac University, 2023)
Minutes of the 22nd Technical and Progress Monitoring (TPM) meeting (session I) of BRACU new campus, held on 31st October, 2019.